Ability to write narrative discourse by using media pictures of students - Amelia Widya Hanindita; Nur Rohmah; Bahauddin Azmy (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research aims to describe the ability to write naration discourse by using media picture in fifth grade students at SDN Dukuh Menanggal I/424 Surabaya. The research design uses a quantitative approach and the type of research is descriptive statistics. The results of the study in general showed that the ability to write naration discourse by using media picture in fifth grade students at SDN Dukuh Menanggal I/424 Surabaya, namely 14 students (50%) were very capable, 7 students (25%) were able, and 7 students (25%) quite capable. As for specifically the abilities of students in (1) detailing and sorting events chronologically, namely (a) on the indicator detailing events 15 students (54%) were able, 13 students (46%) were quite capable; (b) the indicators order events chronologically, namely 20 students (71%) are capable, 8 students (29%) are quite capable; (2) using language, namely (a) on the indicator of the use of letters only 1 student (3.5%) is capable, 1 student (3.5%) is quite capable, 26 students (93%) are not able; (b) on the word choice indicator, 16 students (57.1%) were able, 11 students (39.3%) were quite capable, 1 student (3.6%) was not able; (c) on the indicator of using sentences, 17 students (61%) were able, 10 students (36%) were quite capable, 1 student (3%) was not able.